Design and simulation of a micro scale heat exchanger - Abdul Rashid Abu Talib (2017)
Micro heat exchangers are known to benefit HVAC applications because of its superior surface area to volume ratio to dissipate heat away from the system. The design process surfaces a number of fundamental issues due to down scaling which are absent in the macro scale. One of the main concerns is the large pressure drop due to the micro-sized channel hydraulic diameter. In this paper, the required microchannel design is studied through the optimisation of microchannel aspect ratio and the arrangements of the microchannels layout to remove a target 500W of heat. LiBr/water pair is used as the working fluid. Thermal performance of the heat exchanger is evaluated using the conventional ε – NTU method. The geometrical cross-sectional dimensions of the microchannels are optimised with mathematical models in MATLAB. Further analyses are conducted on the varying lengths and mass flow rates with 2-D models in ANSYS Fluent. Finally, three 3-D microchannel arrangements configuration models were introduced in ANSYS Fluent to simulate realistic temperature distributions across the channel. The result of the analyses reveals that microchannel arrangements significantly improve the thermal performance of the micro heat exchanger. Increasing the surface contact between cold and hot fluid improves heat exchange. These microchannels of size 10mm x 1mm x 100mm (HxWxL) each are capable of dissipating 541.79W of heat with an impressive low pressure drop of 22.94 Pa. The LiBr solution temperature drops to 25℃ at the outlet. The current study can provide a useful guideline in the design for micro heat exchangers with various channel layouts to improve its performance and efficiency.